Changes and resistance of the people of the Aymara communities in the Peruvian context - Alanoca-Arocutipa, Vicente; Apaza-Ticona, Jorge; Mamani-Flores, Adderly; Yucra-Cano, Luz Eleana; Machaca-Mamani, Nestor Richar (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to analyze the processes of change and resistance within the Aymara community in the Peruvian context, focusing on the role of education, inequality barriers, and resistance strategies in shaping a plural and intercultural society. Employing an ethnographic and hermeneutic methodology, the study relies on interviews, focus groups, and ethnographic observations to examine and interpret the transformations experienced by the Aymara population. Data were collected across six provinces in the Puno department, involving 30 interviews and three focus groups with Aymara professionals, community leaders, and local authorities. The study highlights three key aspects: the current contextualization of the Aymara in the Peruvian Altiplano, the crucial role of education in driving change, and the identification of inequality barriers and resistance strategies employed by the Aymara to navigate complex and adverse situations. The findings underscore the importance of intercultural education and the resilience of the Aymara in the face of systemic adversity. The Aymara emerge as key actors in promoting alternatives and hope for a more inclusive and equitable future. Their experience reflects their adaptability and resilience, contributing to redefining a societal project that values cultural diversity in a context marked by structural challenges. The study underscores the importance of understanding change and resistance dynamics from an intercultural perspective, emphasizing the role of indigenous peoples in constructing more just and plural societies. The findings offer valuable insights into fostering social transformation in the face of systemic adversity, particularly through education and resistance strategies.